Diagnóstico do ensino de análise linguística no 9° ano do ensino fundamental na Escola Maria Pereira da Silva em Itaituba-PA - LUZ, Jorgeleno Gomes da (2023)
The present work deals with an analysis of the methodologies used in the teaching of linguistic analysis, commonly called grammar teaching, in the 9th year of elementary education at EMEF Maria Pereira da Silva, rural school, located in the Crepurizinho garimpo, SN- Zona Garimpeira , Itaituba – Pará. The research was carried out based on interviews, observations and collected materials, in addition to a bibliographical survey. We sought to identify how teachers deal with grammar teaching in the ninth grade of elementary school and if the way they deal with it brings results, as a parameter, it is associated with theories of authors such as Antunes (2003), Freire (1996), Oliveira (2010 ), Passeggi (2018), among others. From the collected data, we can say that the teaching of linguistic analysis is present in the speeches of the interviewed teachers and is the first step towards a change in practice in the classroom, as opposed to the traditional teaching of grammar.